BALANCING POWER: A COMPREHENSIVE ANALYSIS OF THE RELATIONSHIP BETWEEN THE JUDICIARY AND PARLIAMENT ACROSS DEMOCRATIC SYSTEMS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This extensive article dives deep into the multifaceted relationship between the Judiciary and Parliament. By drawing from diverse global experiences and international standards, we aim to shed light on the delicate balance of power and mutual interactions that underpin the proper functioning of democratic systems. The article examines the roles, responsibilities, powers, challenges, controversies, and debates that shape these two pillars of democracy.